2019
DOI: 10.1016/j.nicl.2019.102050
|View full text |Cite
|
Sign up to set email alerts
|

Corticolimbic circuit structure moderates an association between early life stress and later trait anxiety

Abstract: Each participant was scanned using one of the two identical research-dedicated GE MR750 3T scanner equipped with high-power high-duty-cycle 50-mT/m gradients at 200 T/m/s slew rate, and an eight-channel head coil for parallel imaging at high bandwidth up to 1 MHz at the Duke-UNC Brain Imaging and Analysis Center. For dMRI data, following an ASSET calibration scan, diffusion-weighted images were acquired across two consecutive 2-min 50-s providing full brain coverage with 2 mm isotropic resolution and 15 diffus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
(73 reference statements)
0
9
0
Order By: Relevance
“…As such, the UF plays an important role in “valence‐based biasing of decisions” and in the incorporation of reward and punishment history into memory‐dependent processes (Von der Heide et al., 2013 ). Likewise, higher structural integrity of the UF has previously been shown to protect against the well‐documented relation between childhood maltreatment and later anxiety and stress resilience (Kim et al., 2019 ). Additionally, activity and connectivity of the prefrontal cortex has recently been found to be an important differential susceptibility marker for the effects of environmental influences on child development (Crone et al, 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…As such, the UF plays an important role in “valence‐based biasing of decisions” and in the incorporation of reward and punishment history into memory‐dependent processes (Von der Heide et al., 2013 ). Likewise, higher structural integrity of the UF has previously been shown to protect against the well‐documented relation between childhood maltreatment and later anxiety and stress resilience (Kim et al., 2019 ). Additionally, activity and connectivity of the prefrontal cortex has recently been found to be an important differential susceptibility marker for the effects of environmental influences on child development (Crone et al, 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…To be eligible for the DNS, all participants were free of: (1) medical diagnoses of cancer, stroke, head injury with loss of consciousness, untreated migraine headaches, diabetes requiring insulin treatment, chronic kidney or liver disease, or lifetime history of psychotic symptoms; (2) use of psychotropic, glucocorticoid, or hypolipidemic medication; and (3) conditions affecting cerebral blood flow and metabolism (e.g., hypertension) [ 77 ]. Neither past nor present diagnosis of Diagnostic and Statistical Manual for Mental Disorders, Fourth Edition (DSM-IV) Axis I or select Axis II disorders (borderline and antisocial personality disorders) were exclusion criterion because the DNS seeks to establish broad variability in multiple behavioral phenotypes related to psychopathology [ 79 ]. Categorical diagnoses were assessed by trained staff using the electronic Mini International Neuropsychiatric Interview [ 80 ] and Structured Clinical Interview for the DSM-IV subtests [ 81 ].…”
Section: Methodsmentioning
confidence: 99%
“…All other studies that investigated the neural correlates of resilience to internalizing problems (Keding et al, 2021;Lu et al, 2017), including trait anxiety (M. J. Kim et al, 2019), reported null findings.…”
Section: Structural Mrimentioning
confidence: 96%
“…Two studies investigated the uncinate fasciculus (UF) tract, which connects the orbitofrontal cortex (OFC) to anterior temporal regions. Of these studies, Chahal et al (2021) found that higher UF fiber density and crosssection (a measure of fiber bundle compactness and width) were associated with lower internalizing symptoms in adolescents with high early life stress, whilst Kim et al (2019) found a null effect for UF fractional anisotropy (FA; a measure of the fraction of diffusion that is directionally dependent). Ohashi et al (2019) examined white matter network structure using graph theory and found no difference in global network architecture between resilient and susceptible youths, but resilient youths did show decreased nodal efficiency and centrality in the amygdala as compared to both susceptible youths and healthy controls.…”
Section: Diffusion Tensor Imagingmentioning
confidence: 99%